Rumen Fermentation Pattern in Lambs Fed Maize (Zea Mays) Grain Sprouts to Substitute Conventional Green Fodder and Compounded Feed Mixture - Chethan, K.P.; Gowda, N.K.S.; Prabhu, T.M.; P.K.Malik; N.M.Soren; G.Tirumalaisamy (Indian Journal of Animal Nutrition, 2023)
To investigate the effect of feeding maize (Zea mays) grain sprouts (MGS) on rumen fermentation characteristics in lambs, a feeding trial was conducted for 120 days. Eighteen healthy male lambs of comparable age (local Mandya crossbreed, 3-4 months) and body weight (Av.12 ± 0.2 kg) were randomly allotted in a complete randomized design (CRD) to three dietary groups of six each. The MGS were produced in a polyhouse and harvested on 10th day. The experimental diets were : Control (T1) group lambs were fed with diet comprising conventional green fodder (CGF), finger millet straw (FMS) and compounded feed mixture (CFM) at 50:10:40 ratio, respectively on dry matter (DM) basis (without maize grain sprouts). In treatment group two (T2), proportion of CGF and CFM was reduced by 50% and substituted with 45% MGS on DM basis (CGF, FMS, CFM and MGS on total DM basis was in 25:10:20:45 ratio, respectively). In treatment group three (T3), CGF was completely replaced with MGS (80%) and CFM was reduced to 25% of control (CGF, FMS, CFM and MGS on total DM basis was in 0:10:10:80 ratio, respectively). After 3 months of feeding CH4 emission measurements using SF6 tracer technique was conducted over a period of 10-days successively, so as to get at least 6 days of reading for each animal and simultaneously digestion trial was conducted to assess the intake and digestibility of nutrients. The representative rumen liquor samples at 0, 4 and 8 h post feeding were collected at the end of experiment from three animals of each group to record pH, protozoal count, nitrogen fractions (Total nitrogen, TCA nitrogen, Ammonia nitrogen), TVFA and individual volatile fatty acids (Acetate, Butyrate, Propionate, Valerate and Isovalerate). Results showed significantly lower (P<0.01) DMI (g/d) in T2 and T3 groups (486.5 & 354.3) as compared to control (687.8) respectively. Rumen liquor nitrogen parameters indicated higher concentration of total nitrogen and similar ammonia nitrogen and TCA precipitable nitrogen in MGS fed groups as compared to control. Significantly lower concentrations of TVFA and acetate were found in T3 group as compared to control and T2. Production of methane (g/d) did not differ significantly among the groups. However, when expressed (g/kg) per unit intake of DM and digested nutrients, methane production was significantly (P<0.01) increased in MGS fed groups as compared to control group. It can be concluded that replacement of compounded feed mixture or conventional green fodder by inclusion of maize grain sprouts in the diet of growing lambs was not beneficial in terms of improving the rumen fermentation and methane reduction